Tenant satisfaction towards property management: case study in D'Mall Seri Iskandar, Perak / Nur Alia Burhan - Burhan, Nur Alia (Universiti Teknologi MARA (UiTM), 2025)
Tenant satisfaction in shopping malls is a critical aspect of the mall's overall performance and business. Mall management must ensure the maintenance practice and that all facilities provided are in good condition. This study investigates the ranking factors affecting the tenant satisfaction towards mall management in D'Mall Seri Iskandar in Perak. General inefficiencies in the overall property management framework reduce operational effectiveness and tenant satisfaction. Furthermore, inadequate or reactive maintenance strategies fail to address issues promptly, leading to property degradation and tenant dissatisfaction. Moreover, property management does not align its services effectively with tenant requirements, leading to dissatisfaction and poor service perception. This research aims to determine and rank the factors that affect tenant satisfaction towards mall management in D’Mall Seri Iskandar.